Green Lantern and philosophy : no evil shall escape this book - White, Mark D. (Hoboken, N.J. ; Chichester : Wiley ; John Wiley, 2011)
Explores the philosophical issues embedded in the Green Lantern Corps' stories and characters, from what Plato's tale of the Ring of Gyges tells us about the Green Lantern ring and the desire for power, to whether willpower is the most important strength.
Includes bibliographical references and index
Keywords: Green Lantern (Fictitious character); Comic books, strips, etc -- Moral and ethical aspects; Philosophy in literature